Proceso de atención nutricional en paciente masculino de 68 años de edad con insuficiencia renal crónica más otras comorbilidades colaterales. - Santana Cox, Francisco Fernando (2022)
The present clinical case is based on a 68-year-old male patient with a history of obstructive uropathies, who presented with a clinical picture characterized by nausea and vomiting of food content from two weeks ago. It is diagnosed of chronic renal failure plus other diseases such as hepatic steatosis grade III, bilateral hydronephrosis and prostatic hyperplasia grade IV, which developed from the underlying disease, the objective of this clinical case is to improve and reduce complications of the nutritional condition. and quality of life of the patient. Through nutritional assessment: anthropometry, biochemistry, clinical signs, food consumption, it is evident that he is overweight with a BMI of 25.17 kg/m2 with gynecoid-type cardiovascular risk, biochemistry reported anemia, hyperkalaemia and kidney failure due to urea values. and creatinine altered outside normal ranges. Clinically, a large abdominal tumor was demonstrated without edema, cachexia, mouth and dry skin. There is inadequate food intake with excess protein intake for his kidney condition and other macronutrients. A balanced dietary prescription of 2205 kilocalories was proposed with a contribution of 56 grams of protein, 330.5 grams of carbohydrates and 73.22 grams of lipids, adequate to demand with frequent monitoring control planning.